‘Liquid’ equilibria. New semantics for public spaces in the Apennines - Azzini, Giulia (Ri-Vista. Research for landscape architecture, 2024)
The proposed contribution investigates the role of public space design for the management and regeneration of the river system in Apennine areas: in an environmental crisis and increasing abandonment scenario, water stands as a central issue of critical discussion, representing a valuable source of livelihood and, at the same time, a potential danger for these territories. Through the selection of some significant experiences, in which architectural and landscape design find in the particular antinomian character of water the opportunity for the construction of new balances in the place, an attempt will be made to identify appropriate regenerative strategies to define the 'liquid' public space as a safe place, through the necessary adaptation to the current environmental and climatic conditions, and as an ecosystem, through the re-signification of the delicate relationship between its anthropic and natural components.